Assessment of toxicity and efficacy of combined chemotherapy (teniposide and carboplatin) and radiotherapy in non-small cell lung cancer patients with brain metastases – a pilot study - M. Kowalski, Dariusz; Zajda, Katarzyna; Krzakowski, Maciej; Wierzchowski, Marek; Jaśkiewicz, Piotr; Denisso, Tadeusz (Contemporary Oncology/Współczesna Onkologia, 2001)
The preliminary results of single-institution, prospective phase II clinical study evaluating the efficacy and toxicity of combined chemotherapy and radiotherapy in patients with non-small cell lung cancer and brain metastases were presented. None of the patients in the study had received prior chemotherapy and radiotherapy. The dose of 3000 cGy in 10 fractions (300 cGy each fraction) was delivered to the whole brain. Chemotherapy was administred simultaneously: carboplatin i.v. on day 1 (dose calculated according on Calvert formula AUC =6) and teniposide i.v. at days 1, 3 and 5 (dose 100 mg/m 2 ). Cycles were repeated every 21 days. Fourteen patients entered the study between June 1999 and December 2000. All patients have completed irradiation scheduled. Complete response of the brain lesions was obtained in 1 patient, partial response in 3 patients, stable disease was noted in 5 patients and progressive disease in 1 patient. The time to progression was in a range of 4–48 weeks (median 14.7 weeks), the overall survival time was in a range of 4–68 weeks (median 21.3 weeks). Mainly, haematologic toxicity was observed (neutropenia, thrombocytopenia, anaemia). The promising results of this pilot study deserve confirmation in phase III randomised study in more numerous group of patients.